2018
DOI: 10.1007/s10453-018-9524-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of meteorological conditions on the concentration of alder pollen in Sosnowiec (Poland) in the years 1997–2017

Abstract: The aim of the work was to compare the alder pollen seasons in the years 1997–2017 in Sosnowiec. The measurements of pollen concentration were taken with the volumetric method using Burkard’s apparatus. The impact of atmospheric conditions on the daily alder pollen grain concentration, the annual totals, and the duration of pollen seasons were studied. The dependency between each meteorological condition and different features of the alder pollen season was determined by using Pearson’s correlation coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…As a result, there have been numerous studies concerned with seasonal pollen concentrations, the impact of weather, and modelling of airborne alder pollen (Rodriguez-Rajo et al 2009;Nowosad et al 2018). In a temperate climate, the average start dates of the Alnus pollen season are highly variable, ranging from December to March or April (Jantunen et al 2012;Gehrig et al 2015;Dąbrowska-Zapart et al 2018). In Poland, the pollen season starts on average at the beginning of March and lasts until the second half of April, while maximum pollen concentrations occur during the last 10 days of March (Nowosad et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there have been numerous studies concerned with seasonal pollen concentrations, the impact of weather, and modelling of airborne alder pollen (Rodriguez-Rajo et al 2009;Nowosad et al 2018). In a temperate climate, the average start dates of the Alnus pollen season are highly variable, ranging from December to March or April (Jantunen et al 2012;Gehrig et al 2015;Dąbrowska-Zapart et al 2018). In Poland, the pollen season starts on average at the beginning of March and lasts until the second half of April, while maximum pollen concentrations occur during the last 10 days of March (Nowosad et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Her analysis has shown that even a small increase in temperature or more sunlight favours pollination and an earlier start to the season of Corylus (Kasprzyk 2010). Pollen grain concentration is sensitive to temperature, which was confirmed by Dąbrowska-Zapart et al (2018) for Alnus and by Gottardini and Cristofolini (1997) for Corylus. In our study, we observed the negative significant correlation between Corylus pollen concentrations and daily minimum temperature.…”
Section: Discussionmentioning
confidence: 74%
“…Malkiewicz et al (2016) stated that with regard to the presence of Alnus and Corylus pollen in the air, the greatest influence has thermal factor. According to Dąbrowska-Zapart et al (2018), except the temperature, their studies showed also a statistically significant correlation coefficient between the amount of alder pollen grains and the weather front type. Puc and Kasprzyk (2013) compared pollen concentration and the meteorology for two cities in Poland (Szczecin and Rzeszów).…”
mentioning
confidence: 97%
See 2 more Smart Citations